Early “Rootprints” of Plant Terrestrialization: Selaginella Root Development Sheds Light on Root Evolution in Vascular Plants - Fang, Tao; Motte, Hans; Parizot, Boris; Beeckman, Tom (Frontiers in Plant Science, 2021)
Roots provide multiple key functions for plants, including anchorage and capturing of water and nutrients. Evolutionarily, roots represent a crucial innovation that enabled plants to migrate from aquatic to terrestrial environment and to grow in height. Based on fossil evidence, roots evolved at least twice independently, once in the lycophyte clade and once in the euphyllophyte (ferns and seed plants) clade. In lycophytes, roots originated in a stepwise manner. Despite their pivotal position in root evolution, it remains unclear how root development is controlled in lycophytes. Getting more insight into lycophyte root development might shed light on how genetic players controlling the root meristem and root developmental processes have evolved. Unfortunately, genetic studies in lycophytes are lagging behind, lacking advanced biotechnological tools, partially caused by the limited economic value of this clade. The technology of RNA sequencing (RNA-seq) at least enabled transcriptome studies, which could enhance the understanding or discovery of genes involved in the root development of this sister group of euphyllophytes. Here, we provide an overview of the current knowledge on root evolution followed by a survey of root developmental events and how these are genetically and hormonally controlled, starting from insights obtained in the model seed plant Arabidopsis and where possible making a comparison with lycophyte root development. Secondly, we suggest possible key genetic regulators in root development of lycophytes mainly based on their expression profiles in Selaginella moellendorffii and phylogenetics. Finally, we point out challenges and possible future directions for research on root evolution.